Gugging : Art Brut der Gegenwart. - Galerie Rigassi AG, Bern (Bern : Edition Galerie Rigassi AG, 1994)
Fischer, Johann ; Garber, Johann ; Hauser, Johann ; Kamlander, Franz ; Kernebeis, Franz ; Korec, Johann ; Reisenbauer, Heinrich ; Schmidt, Arnold ; Tschirtner, Oswald ; Walla, August
Gugging : Art Brut der Gegenwart, Galerie Rigassi AG, Bern, 15. Juni bis 31. Juli 1994
boek